Optimalisasi Dosis Pupuk Tunggal dan Pupuk Kandang untuk Produksi Bawang Putih di Dataran Tinggi - Ika Cartika; Abdi Hudaya; Fahmi Aprianto; Rini Murtiningsih (UM Purwokerto Press, 2021)
The addition of nutrients for garlic plants consists of two type, namely the application of anorganic fertilizers in the form of single fertilizers N, P, K and organic fertilizers such as manure. The purpose of this study was to obtain the right dose of single fertilizer N, P, K and chicken manure. The experiment was arranged using a Randomized Block Design with 4 replications. The treatments consisted of 9 treatment combinations consisting of A = 100% single fertilizer + 15 tons of manure, B = 100% single fertilizer + 10 tons of manure, C = 100% single fertilizer + 5 tons of manure, D = 75% single fertilizer + 15 tons of manure, E = 75% single fertilizer + 10 tons of manure, F = 75% single fertilizer + 5 tons of manure, G = 50% single fertilizer + 15 tons of manure, H = 50% single fertilizer + 10 tons of manure, I = 50% single fertilizer + 5 tons of manure. The dose of 100% single fertilizer was SP36 375 kg.ha-1, ZA 1.144 kg.ha-1and KCl 200 kg.ha-1. The type of manure used is chicken manure. The results showed that doses of 75% and 100% of single fertilizer combined with 15 ton.ha-1 resulted in the wet and dry weight of the stover, the diameter and weight of the tubers, which were the same, respectively, the dry weight of the stover 32,57 grams and 39,40 grams, the dry weight of the stover. 17,43 grams and 17,63 grams, tuber diameter 33,09 and 33,13, tuber weight 14,07 grams and 14,30 grams. These results tend to be higher than other treatments. 75% single fertilizer and 15 ton.ha-1 chicken manure can be recommended for fertilization in garlic production.